COMPARISON OF ENCRYPTION ALGORITHMS ON NoSQL DATABASES - Kannan, P. Rajesh; Mala, R (International Journal of Computer Sciences and Engineering, 2025)
Security has become one of the key features of data transmission on large databases. Sensible data that are available in the form of documents or unstructured format must be shared among the users in a confidential manner. NoSQL databases are nowadays popular in handling the unstructured data that are available as open source databases such as MongoDB, Cassandra, Redis etc. This paper make a detailed study on the encryption techniques of NoSQL databases especially MongoDB which becomes popular in data management. Since encryption features are not applied on handling the data in MongoDB, the various encryption techniques proposed on securing the sensitive data at rest and at transit are compared based on different encryption algorithms